Black writers in Britain, 1760-1890 - Edwards, Paul, 1926-1992.; Dabydeen, David (Edinburgh : Edinburgh University Press, 1991)
Containing extracts from all the major Afro-British writers and many early Black American, West African and Caribbean writers who spent time in Britain, this anthology is a sparkling introduction to the rich tradition of Black British writing. A general introduction to the anthology discusses the beginnings of Black literature in Britain during the period of Abolition. Each author in the anthology also has an individual introduction which briefly examines the author and the period in which he or she was writing, as well as the extract itself. The anthology is drawn from autobiographies, slave narratives, unpublished letters, oral accounts and public records, and represents the work of people such as Equiano, Cugoano, Sancho, Gronniosaw, Robert Wedderburn, James Africanus Horton, Mary Prince, Mary Seacole, Harriet Jacobus, Edward Wilmot Blyden and John E. Ocansey.
The Writers. 1. Briton Hammon. 2. Ukawsaw Gronniosaw (James Albert). 3. Ignatius Sancho. 4. Ottobah Cugoano (John Stuart). 5. Olaudah Equiano (Gustavus Vassa). 6. Julius Soubise. 7. Sierra Leone Settlers. 8. John Henry Naimbanna. 9. Philip Quaque. 10. John Jea. 11. William Davidson. 12. Robert Wedderburn. 13. Mary Prince. 14. Mary Seacole. 15. Harriet Jacobs (Linda Brent). 16. James Africanus Horton. 17. John E. Ocansey. 18. Edward Wilmot Blyden. 19. J.J. Thomas.
Includes bibliographical references (pages 236-239).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: English literature -- Black authors; Black people -- Great Britain -- Literary collections; English literature -- 19th century; English literature -- 18th century; English literature -- Black authors -- History and criticism; English literature -- 18th century -- History and criticism; English literature -- 19th century -- History and criticism; Littérature anglaise -- Auteurs noirs -- Histoire et critique; Littérature anglaise -- 18e siècle -- Histoire et critique; Littérature anglaise -- 19e siècle -- Histoire et critique; Littérature anglaise -- Auteurs noirs; Littérature anglaise -- 19e siècle.; Littérature anglaise -- 18e siècle.; LITERARY COLLECTIONS -- General; Black people; English literature; English literature -- Black authors; Great Britain; Literatur; Schriftsteller; Großbritannien; Schwärze; Littérature anglaise -- Auteurs noirs; Littérature anglaise -- 18e siècle -- Histoire et critique; Littérature anglaise -- 19e siècle -- Histoire et critique; Englisch; 1700-1899; Geschichte 1760-1890.; 16th to 18th century texts; 19th century texts; Black studies; Criticism, interpretation, etc; Literary collections